Created by alex.examtime9373
almost 6 years ago


Equation 1: v = u + at Definition of acceleration > a = (vu)/t Multiply both sides by t > at = vu Add u to both sides > v = u + at
Equation 2: s = ut + (1/2)at² Definition of displacement > s = {(u + v)/2}t Use equation 1 & substitute 'u + at' for v > s = {(u + u + at)/2}t Multiply out the brackets > s = (2ut + at²)/2 Divide top and bottom lines by 2 > s = ut + (1/2)at²
Equation 3: v² = u² + 2as Equation 1 > v = u + at Square both sides > v² = (u² + 2uat + a²t²) v² = u² + 2a{ut + (1/2)at²} Use equation 2 and substitute ' s ' for ' ut + (1/2)at² ' > v² = u² +2as
New Page